Reducing the Effects of Strawberry Juice's Antioxidant Qualities on Rabbits' Renal and Hemotoxic Reactions Caused by Carbon Tetrachloride - Fayrouz Khaled,; Ramadan Ali,; Tahani Aboulqassim3, (AlQalam Journal of Medical and Applied Sciences, 2025)
Strawberries (Fragaria × ananassa) are rich in polyphenols and antioxidants that may protect against oxidative stress, while carbon tetrachloride (CCl₄) is a well-known hepatotoxin used experimentally to induce liver and kidney injury. This study evaluated the protective effects of strawberry juice against CCl₄-induced hepatic and renal dysfunction in male rabbits. Biochemical analysis revealed that CCl₄ significantly elevated serum levels of aspartate transaminase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALK), indicating hepatic injury. Specifically, AST and ALT levels were markedly increased in the CCl₄ group compared to controls, while treatment with strawberry juice alone significantly reduced these enzymes below control values. Co-administration of strawberry juice with CCl₄ resulted in AST and ALT levels nearly normalized to the control, indicating a hepatoprotective effect. Interestingly, ALK activity was highest in the strawberry juice group, suggesting enhanced biliary function, while the lowest ALK activity in the CCl₄ group implied possible cholestasis. In combination, ALK levels returned to near-normal values. Renal and metabolic parameters also demonstrated notable changes. CCl₄ significantly elevated plasma glucose, creatinine, and urea levels, indicative of metabolic disruption and renal impairment. Strawberry juice alone lowered these markers significantly, while co-administration with CCl₄ restored glucose, creatinine, and urea levels toward control values. These findings suggest that strawberry juice exerts both hepatoprotective and renoprotective effects, potentially through its antioxidant and anti-inflammatory properties.